Race, masks, residency and concern regarding COVID‐19 transmission. Issue 4 (18th October 2022) - Azhar, Sameena; Rahman, Rahbel; Wernick, Laura J.; Tripathi, Saumya; Cohen, Margaret; Maschi, Tina
Abstract: To explore sociodemographic predictors for concern regarding COVID‐19 transmission and how these factors interact with the identities of others, we conducted a web‐based survey where we asked 568 respondents in the United States to indicate their level of COVID‐19 concern in response to a series of images with short vignettes of masked and unmasked individuals of different racial/ethnic backgrounds. Using a linear mixed effects model, we found that regardless of the race of the image being presented in the vignette, concern regarding COVID‐19 transmission was associated with respondents' older age ( b = 0.029, p < 0.001), residing in NYC ( b = 0.556, p = 0.009), being heterosexual ( b = 1.075, p < 0.001), having higher levels of education, that is, completion of a Bachelor's degree ( b = 1.10, p = 0.033) or graduate degree ( b = 1.78, p < 0.001), and the person in the vignette being unmasked ( b = 0.822, p < 0.001). Asian respondents were more likely than White respondents to be concerned regarding COVID‐19. Individuals who self‐reported themselves to be at high risk for COVID‐19 were more likely to be concerned about COVID‐19 over those who considered themselves to be low risk. These findings highlight the importance of acknowledging interactions between race, mask status, and residency in predicting COVID‐19 concern.